Production of a Plasma Derived Universal Antivenom against All Elapid Neurotoxic Snake Venoms: Universal snake antivenom - Ratanabanangkoon, Kavi (Siriraj Medical Bulletin, 2021)
Snakebite envenoming has killed about 138000 people and maimed 400,000 victims annually. WHO has designated this medical problem as one of the most neglected tropical diseases for which effective, affordable antivenoms (AVs) are urgently needed. Production of potent AV against neurotoxic venoms was difficult and was thought to be due to the low immunogenicity of the postsynaptic neurotoxins (PSNT) which cause death in the victims. However, it was showed that the use of ineffective adjuvant in the immunization of horse was the root cause. The highly effective Freund adjuvant (FA) causes severe local reactions and could not be used. A novel immunization protocol termed ‘low dose low volume multi-site’ was tested and shown to obliterate the local side effect and allow for the safe use of FA in horse. The immunization protocol led to the production of 7 highly potent monovalent AVs, and 2 potent polyvalent AVs, one against 4 neurotoxic venoms and another against 3 hematotoxic venoms. These AVs allow the treatment of snakebite victims without the need to identify the culprit snakes. Furthermore, we have tested a novel immunization strategy using ‘Diverse toxin repertoire’ of 12 Asian elapid toxin fractions. The resulting antiserum effectively neutralized at least 36 elapid venoms of 28 species encompassing 10 genera and from 20 countries on 4 continents, and most likely all the elapid neurotoxic snake venoms. These results indicate that effective universal antivenom against all elapid neurotoxic venoms of the world can be produced and save numerous lives.